Eurasian badger habitat selection in Mediterranean environments: Does scale really matter? - Rosalino, L. M.; Santos, Maria J.; Beier, P.; Santos-Reis, Margarida (Mammalian Biology - Zeitschrift für Säugetierkunde, 2008)
It is widely believed that spatial scale affects habitat selection, and should inﬂuence management options, especially for species with wide geographic distribution or large territories. Eurasian badger habitat selection has been well studied throughout most of its European distribution range, but never at multiple spatial scales. We used compositional analysis to assess habitat selection of Eurasian badgers in southern Portugal at four spatial scales (1, 4, 25, and 100 km 2 ). We assessed habitat use from setts, latrines and footprints presence, and road kills. Oak woodlands with understorey were selected at all scales, being the most preferred habitat at 3 scales (1, 4, and 100 km 2 ). Pastures were most selected at the scale of the 25 km 2 cell, but their use was not signiﬁcantly different from oak woodland with understorey. Shrubs and pastures were also secondly important at the majority of scales. Contrary to ﬁndings at northern latitudes, deciduous forests decreased in importance as cell size increased. In the highly humanized and fragmented landscape of southern Portugal, Eurasian badgers are selecting the matrix of oak woodlands interspersed with patches of pastures, shrubs and riparian vegetation. In these oak woodlands, scale does not have a marked effect. Management for badgers should provide, for at least, 30% of oak woodland cover at all scales. Our study illustrates the across-scale importance of maintaining the historically human altered, sustainable and unique landscape and land use system – the montado.
Keywords: landscape ecology; meles meles; montado; Portugal